Cognitive and technological recourses in teachers’ adaptation to emergency remote teaching - Eden, Sigal (Frontiers in Education, 2024)
This study investigates the impact of the abrupt transition to emergency remote learning (ERT), specifically focusing on teachers' cognitive resources and technological resources both before and during ERT. The sample comprised 1,071 teachers: before ERT (53.0%), during ERT (47.0%). Five questionnaires were administered. Results indicated that teachers surveyed during ERT, compared to their counterparts surveyed before ERT, exhibited significantly elevated attitudes toward information and communication technology (ICT), increased usage of the online environment for teaching and use of computers for communication.Additionally, the degree of readiness for educational change significantly contributed to the teachers' changed attitudes toward ICT.